2013
DOI: 10.1073/pnas.1214547110
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tumor growth and metastasis by a self-therapeutic nanoparticle

Abstract: Although biomedical applications of nanotechnology, which typically involve functionalized nanoparticles, have taken significant strides, biological characterization of unmodified nanoparticles remains underinvestigated. Herein we demonstrate that unmodified gold nanoparticles (AuNPs) inhibit the proliferation of cancer cells in a size-and concentration-dependent manner by abrogating MAPK-signaling. In addition, these AuNPs reverse epithelial-mesenchymal transition (EMT) in cancer cells by reducing secretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
217
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(228 citation statements)
references
References 52 publications
7
217
3
1
Order By: Relevance
“…The ability to control the unique toxicity profiles of different nanomaterials will allow us to exploit specific vulnerabilities in cancer cells in a highly selective manner. 20,21 In support of this concept, recent studies have shown that gold nanoparticles alone can inhibit ovarian tumor growth and metastasis in mice. 21 Additionally, several groups showed that AgNPs have anti-breast cancer activity, [5][6][7] but concerns over the safety profile of AgNPs have limited their clinical translation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The ability to control the unique toxicity profiles of different nanomaterials will allow us to exploit specific vulnerabilities in cancer cells in a highly selective manner. 20,21 In support of this concept, recent studies have shown that gold nanoparticles alone can inhibit ovarian tumor growth and metastasis in mice. 21 Additionally, several groups showed that AgNPs have anti-breast cancer activity, [5][6][7] but concerns over the safety profile of AgNPs have limited their clinical translation.…”
Section: Discussionmentioning
confidence: 83%
“…However, the unique toxicity profiles of nanoparticles may also offer an opportunity to exploit specific vulnerabilities in cancer, provided that an appropriate disease target could be identified. 20,21 In this case, the nanomaterial itself would act as the therapeutic agent. Exposure of cells to AgNPs has been reported to cause DNA damage and induce oxidative stress, 22,23 and cells deficient in their capacity to repair DNA damage are and resistance to established therapies and dose-limiting toxic side effects frequently occur, new therapeutic agents are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their small size and surface modifications, nanoparticles, in general, are able to target tumors selectively (15) and have been widely used in cancer diagnosis and therapy (16,17). The recent discovery of nanoparticles' effect on inhibiting cancer cell migration or metastasis starts to draw the attention of researchers (18)(19)(20)(21)(22). However, high concentrations of nontargeted nanoparticles (in ÎźM) were used in these previous studies, which might be an obstacle when considering the translation to clinical use.…”
mentioning
confidence: 99%
“…Although cancer treatment strategies using functionalized nanoparticles have been significantly studied, the effect of un-modified bi-metallic nanoparticles remains under investigated (Arvizo et al 2013). Nanoparticles have been considered as the most prominent vehicle for targeted drugdelivery in cancer cells due to their unique properties of passing the biological barriers and distribution within the cellular counterparts through receptor-mediated or energydependent pathways (Bhattacharya and Mukherjee 2008).…”
Section: Introductionmentioning
confidence: 99%